2020
DOI: 10.5713/ajas.19.0392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Antrodia cinnamomea fermented product supplementation on antioxidation, anti-inflammation, and lipid metabolism in broiler chickens

Abstract: Objective: This study was investigated the effects of dietary supplementation of Antrodia cinnamomea fermented product on modulation of antioxidation, anti-inflammation, and lipid metabolism in broilers.Methods: Functional compounds and in vitro antioxidant capacity were detected in wheat bran (WB) solid-state fermented by Antrodia cinnamomea for 16 days (FAC). In animal experiment, 400 d-old broiler chickens were allotted into 5 groups fed control diet, and control diet replaced with 5% WB, 10% WB, 5% FAC, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Agricultural by-products, such as Wheat Bran (WB), contain Non-Starch Polysaccharides (NSPs) that act as anti-nutritional compounds in monogastric animals, which tend to inhibit digestibility and promote pathogen proliferation in the gastrointestinal tract, and eventually lead to gut inflammation and worsen the performance of the animals [ 8 , 9 ]. Solid-State Fermentation (SSF) could represent a valuable method to use agricultural by-products as substrates for NSP-degrading microorganisms, converting them into alternative feed ingredients [ 10 , 11 ]. In addition, filamentous fungi were reported as being a suitable inoculant for SSF due to their ability to withstand low humidity environments [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural by-products, such as Wheat Bran (WB), contain Non-Starch Polysaccharides (NSPs) that act as anti-nutritional compounds in monogastric animals, which tend to inhibit digestibility and promote pathogen proliferation in the gastrointestinal tract, and eventually lead to gut inflammation and worsen the performance of the animals [ 8 , 9 ]. Solid-State Fermentation (SSF) could represent a valuable method to use agricultural by-products as substrates for NSP-degrading microorganisms, converting them into alternative feed ingredients [ 10 , 11 ]. In addition, filamentous fungi were reported as being a suitable inoculant for SSF due to their ability to withstand low humidity environments [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The solid-state fermentation ( SSF ) process uses low-cost agricultural and agroprocessing waste as substrates by applying NSP-degrading microorganisms to improve the utility of those by-products. Compared with the submerged fermentation, SSF is more efficient and cost effective in producing bioactive compounds ( Hölker et al., 2004 , Lee et al., 2020a ). Filamentous fungi were reported to be the most suitable for SSF owing to their ability to endure low-moisture fermentation environments ( Hernández et al., 2008 , Lee et al., 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the submerged fermentation, SSF is more efficient and cost effective in producing bioactive compounds ( Hölker et al., 2004 , Lee et al., 2020a ). Filamentous fungi were reported to be the most suitable for SSF owing to their ability to endure low-moisture fermentation environments ( Hernández et al., 2008 , Lee et al., 2020a ). Our previous studies had reported the application of SSF using filamentous fungi on agricultural byproducts which further exerted positive effects on monogastric animals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations